Organic photovoltaic devices with a crosslinkable polymer interlayer - Kang, Nam Su; Ju, Byeong-Kwon; Lee, Tae Wan; Choi, Dong Hoon; Hong, Jae-Min; Yu, Jae-Woong (ELSEVIER SCIENCE BV, 2011)
Organic photovoltaic devices with a photo-crosslinkable interlayer were fabricated. This photo-crosslinkable interlayer acted as a leakage current reducing buffer layer. The performance of the small area OPV cell (0.04 cm(2)) was enhanced by the increase in the short circuit current and the fill factor. When a larger area cell (1 cm(2)) was used, the performance of OPV cell increased when the appropriate interlayer thickness was used. In the case of a 10 cm x 10 cm module, the power conversion efficiency was about double than that without the interlayer. The insertion of the interlayer increased the current extraction by lowering the barrier height and attenuated the fill factor reduction by enhancing the rectification with a better leakage current sealing. From this study, it is clearly proved that the insertion of the appropriate photo-crosslinkable layer improves the performance of OPV devices, the effect was especially evident for large area cells. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: HETEROJUNCTION SOLAR-CELLS; ENERGY-CONVERSION EFFICIENCY; SELF-ORGANIZATION; MORPHOLOGY EVOLUTION; BULK HETEROJUNCTIONS; CONDUCTING POLYMER; DESIGN RULES; BLENDS; PERFORMANCE; NETWORK